SAMPAH DAN PENGARUHNYA TERHADAP KUALITAS AIR DANAU LIMBOTO - L, Chairunnisa J (Jurnal Entropi, 2006)
The aim of this research was toknow garbage influence to water quality of Limboto lake on Gororntalo province. The samples wew taken in part of surface, middle and base of the lake. The methods were base on qualitatitive and quantitative methods. The analyze of sedimentatiton, temperature and pH used quantitative methods. The changes of colour, aroma and turbidity on Limboto lake detected base on qualitative methods. The coliform bacteria detected base on qualitative and quantitative on the laboratory.Result of this research show as the both research location has experienced turbidity, colour and aroma. The area was not having garbage higher of temperature than the one. On the contrary, the area having garbage higher sedimentation of than the one. Chemical analyze has similar pH on the both locations. The qualitative and quantitative analyze of Coliform bacteria show area research >24.00 sel.ml-1 water. Thet means, Limboto lake has passed thershold value base on regulation of govern ments no. 82 the year 2001. Therefore, the publics around of Limboto lake expected keep cleaning and prevent contamination of the lake.